THE SEMIEMPIRICAL MODEL OF THE MULTICOMPONENT BUBBLE BEHAVIOUR IN GLASS MELTS - LUBOMÍR NĚMEC; MIROSLAVA VERNEROVÁ; PETRA CINCIBUSOVÁ; MARCELA JEBAVÁ; JAROSLAV KLOUŽEK (Ceramics-Silikáty, 2012)
A semi-empirical model of the bubble growth and dissolution in glasses with a fining agent has been derived. This model applies the experimental data from bubble observation at melting and fining temperatures. The experimental data needed for the model involved the temperature dependences of the average growth rate of the bubble radius and the average concentration of the fining gas in the bubbles. Both sets of values were measured in the laboratory in the glass of the float type and applied in the model. The measurements of the solubilities and diffusion coefficients of the gases present in the glass – needed for the analytical model of multicomponent bubbles – were thus avoided. The course of the partial bubble absorption with the temperature decreasing was simulated by means of two factors modifying the experimental values of the bubble growth rates at constant temperature. The temperature dependence of the resulting bubble growth rate qualitatively corresponded to the experimental observations in the soda-lime-silica glass, but a more detailed experimental and comparative study has yet to be performed. Such a study is being prepared.